Beyond infant death: the hidden costs of male immigration in geladas. (January 2020) - Schneider-Crease, India; Chiou, Kenneth L.; Snyder-Mackler, Noah; Bergman, Thore J.; Beehner, Jacinta C.; Lu, Amy
Abstract : The experience of traumatic events can catalyse physiological trade-offs that increase the vulnerability of organisms to disease and death. Among potential sources of trauma, the arrival of new males in female-philopatric species may be particularly salient due to the accompanying threat of infanticide. In such social systems, the killing of dependent offspring benefits these new males by accelerating females' return to receptivity. Despite widespread interest in the evolutionary drivers of infanticide, there is little known about the collateral effects of male immigration on other group members. That is, do the periods following male immigration act as 'windows of adversity' that carry costs for group members over and above the direct victims of infanticide? Here, we examined how the immediate aftermath of new male immigration in a female-philopatric species ( Theropithecus gelada ) was related to the risk of injury for all individuals. Analysing 139 injuries and 41 male immigration events across 9 years of data collection, we found that male immigration was accompanied by increases in injury risk for all natal individuals (adult males were excluded from the analysis), with the most severe effects for dependent infants and lactating females. Females with injuries had longer interbirth intervals, highlighting the reproductive consequences of injury. This study is among the first to quantify costs associated with male immigration beyond infant mortality and highlights that these periods can act as windows of adversity that may affect lifetime health and fitness outcomes. Highlights: Injury risk increased for all group members following male immigration in geladas. Dependent infants and lactating females incurred the most injuries. Injured females had longer interbirth intervals. Our results reveal a link between male immigration and female reproductive fitness.